The Byzantine antiquarian: a case study of a compiled colophon - Boeten, Julie (Byzantinische Zeitschrift, 2019)
In this article, we present a colophon epigram found in the manuscript Napoli, Biblioteca Nazionale, gr. II C 33. We edit the text, provide a translation and commentary and supply it with a thorough metrical analysis. Throughout the article, we investigate whether the scribe meant this colophon to be one text or three separate texts. By doing so, we will touch upon broader issues, such as Byzantine metrics in general and the Byzantine habit of compiling texts from an antiquarian perspective.null